Techno-Economic Investigation of Standalone Photovoltaic Energy Systems for Rural Areas of Quetta - Riaz Ahmed; Abdul Basit; Qamar ud Din Abid; Muhammad Haroon; Fasihullah Kakar; Najeeb Ullah; Danish Ahmed Khan (Engineering Proceedings, 2023)
The purpose of this techno-economic study is to investigate the potential of the implementation of standalone photovoltaic (PV) energy systems in rural areas of Quetta, Pakistan. This study focuses on alleviating the region’s energy crisis and giving the local population access to clean and sustainable energy. The technique used entails data collection, load demand analysis, technical and economic evaluation, site selection, and data interpretation. The findings and discussion provide an estimate of PV energy systems’ lifetime costs, annual maintenance expenses, and energy prices. The results show that standalone PV energy systems are a feasible and financially viable option for electricity generation in Quetta’s rural areas that operates via monitoring the economic development and environmental sustainability of the region. Three plants are proposed for generating 26.8 KW, 15 KW, and 6.8 KW of power, and it is demonstrated that green and clean energy can be provided for domestic consumers at reasonable unit costs of PKR. 21.33, PKR. 21.9, and PKR. 23.89, respectively.